Experiencing circular design: Stories of agri-food waste transformed into new materials for architecture - Silvia Tedesco; Elena Montacchini; Jacopo Andreotti (Acta Polytechnica CTU Proceedings)
The application of the Circular Economy model, supported by the European Commission, can be the driver of an industrial and architectural conversion and, also, an opportunity to innovate production processes through the elimination of the concept of waste. Furthermore, the attention of public and private actors as well as policies and rules are now focused on accelerating the ongoing transition from linear to circular economy. In line with this multi-sectoral shift, the paper intends to illustrate the results of the research activities carried out at the Politecnico di Torino in cooperation with Small and Medium Enterprises (SMEs) of the Piedmont region (Italy). In particular, the article illustrates a double experience developed with two different paths: the CIBUS’ research project (Circular economy in the Building Sector from agri-food waste) and the innovative master’s degree course Design and development the transition to the circular economy. Both experiences apply circular economy approaches to grape, hazelnut, and wheat waste to understand whether they could be new “ingredients” for architecture and design.